PNEUMONIA IN PATIENTS WITH LIVER CIRRHOSIS - R. V. Kazakova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
This paper presents a review of the scientific literature on the pathogenesis, diagnosis and treatment of pneumonia in liver cirrhosis. Pneumonia occur in 4-21% of patients with cirrhosis of the liver, the most common etiology of alcohol. Often the development of pneumonia complicated by bleeding from varicose veins in the esophagus. Mortality rate is 40%, the risk factors of mortality are impaired consciousness, mnogodolevaya pneumonia, ascites, acute renal failure, bacteremia, length of hospital stay. Separately considering other options lung disease in patients with liver cirrhosis (hepatopulmonary syndrome and portopulmonary hypertension), as well as other causes of fever in liver disease. An algorithm for investigation of patients with abnormal liver function, and fever, which includes finding the source of infection, diagnosis of bacterial overgrowth syndrome, bacterial translocation and endotoxemia, and consideration of possible non-infectious causes of fever.